Obstructive Sleep Apnea Syndrome and Cardiovascular Diseases; the Role of Hypertension - Yasemin Dinç; Aylin Bican Demir (Türk Uyku Tıbbı Dergisi, 2022)

(untitled)
Objective:Obstructive sleep apnea syndrome (OSAS) is a common disorder that results from the collapse of the upper airways during sleep and causes temporary hypoxia. OSAS and hypertension are common and multifactorial diseases. aim This study aimed to determine the clinical, demographic, polysomnographic and prognostic features of OSAS patients with hypertension.Materials and Methods:In this study, 364 patients diagnosed with OSAS in the sleep laboratory of the Department of Neurology, Bursa Uludağ University Faculty of Medicine between 2016 and 2021 were retrospectively scanned and included. The patients were analyzed by comparing them with and without hypertension.Results:When patients with and without hypertension were compared according to clinical, demographic and polysomnography data, age (p<0.001), sex (p=0.009), presence of diabetes mellitus (DM) (p<0.001), presence of coronary artery disease (p<0.001), presence of heart failure (p=0.020), presence of atrial fibrillation (p=0.004), ischemic stroke (p<0.001), minimum oxygen saturation (p=0.015), oxygen desaturation index (p=0.034) and body mass index (BMI) (p<0.001) were statistically significantly correlated. When the significant variables were analyzed with binary logistic regression, the most significant variables were age [p<0.001, odds ratio (OR): 1.07], DM (p<0.001, OR: 7.58), coronary artery disease (p=0.003, OR: 4.92), heart failure (p=0.041, OR: 5.53), ischemic stroke (p=0.042, OR: 3.38) and BMI (p<0.001, OR: 1.28).Conclusion:In this study, we found that cardiovascular diseases such as coronary artery disease, heart failure and ischemic stroke are more common in OSAS patients with hypertension, and this is independent of risk factors such as age, DM and BMI. OSAS and cardiovascular diseases may show ethnic and racial differences. For this reason, we suggest conducting multicenter prospective studies examining the effects on blood pressure regulation and cardiovascular diseases in our own population.